2003
DOI: 10.1063/1.1545441
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved B̃–X̃ electronic spectra of both conformers of the 1-propoxy radical

Abstract: Five bands of the B̃–X̃ laser induced fluorescence spectrum of jet-cooled 1-propoxy radical have been recorded with a spectral resolution of ≈200 MHz. The resolved rotational and fine structure of these bands has been assigned and analyzed providing rotational constants for both the X̃ and B̃ states as well as components of the electron spin-rotation tensor in the X̃ state. By comparison of these constants with ones obtained from quantum chemistry calculations, two bands have been assigned to the gauche (G) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 26 publications
6
65
0
Order By: Relevance
“…We reported a similar observation in the case of 1-propoxy. 17 In that work, the difference in rotational stucture between different groups of vibronic bands was confirmed to be due to the two different conformers of the 1-propoxy radical by means of detailed rotational analysis. It is likely that the three sets of bands of 1-butoxy shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…We reported a similar observation in the case of 1-propoxy. 17 In that work, the difference in rotational stucture between different groups of vibronic bands was confirmed to be due to the two different conformers of the 1-propoxy radical by means of detailed rotational analysis. It is likely that the three sets of bands of 1-butoxy shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
“…This band is analogous, in terms of rotational structure, to band B of 1-propoxy whose carrier was likewise shown to be a C s trans conformer. 17 In that work we demonstrated that all six rotational constants can be determined in principle from the spectra and a similar argument holds for 1-butoxy. As suggested by Table 1, all conformers of 1-butoxy are near prolate symmetric tops.…”
Section: Rotational Structurementioning
confidence: 92%
See 3 more Smart Citations